Madu sebagai Wet Batter pada Produk Udang Breaded - Nadia Gustina; Kiki Yuliati; Shanti Dwita Lestari (Jurnal FishtecH, 2015)
The purpose of this research is to determine the effect honey as a wet batter on the breaded shrimp quality. The research was conducted from February 2014 until September 2014. The results showed that were analyzed using randomized complete block design (RCBD). Parameters observed were chemical analysis (moisture content), pH measurement, water activity (aw), analysis of microbiological (TPC) and sensory analysis. Chemical characteristics of breaded shrimp in this study with the average of water content between 67.27% - 80.25%, pH value was 6.45 – 7.98, the average value of water activity (aw) was 0.73 – 0.97. While the values of the sensory analysis was 3.6 – 8.6.